Relationship of Postpartum Knowledge and Giving Colostrum to New-Born Babies - Fitriyani Djunaid; Masmuni Wahda Aisyah; Ulfiana Djunaid (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Factors knowledge, age, education, and information can affect the mother does not give colostrum to newborns. As a result, mothers do not give colostrum to their babies. The purpose of this study was to determine the relationship of knowledge of postpartum mothers with the provision of colostrum in newborns. The type of this research was survey research with a Cross-Sectional Study approach, with a total sample of 64 postpartum mothers. The result of the research is based on Chi-Square statistical test with significance level: α = 0,05 and df = 1, it is found that X2 count X2 table (5,534 3,841) hence Ho rejected means there is a relationship between Knowledge of Post Partum Mother with Colostrum Giving to new baby Born in Mother Hospital of Gorontalo City Year 2015. Conclusion there is the relation between Knowledge of mother of postpartum By giving colostrum to a newborn baby in obstetric room General Hospital of Bunda Town Gorontalo Year 2015.